Penerjemahan Kata Budaya dalam Laskar Pelangi ke Dalam Novel Bahasa Jepang Niji No Shoonentachi - Nurjana, Mike (Paradigma: Jurnal Kajian Budaya, 2017)
This research aims to describe the method and technique of the translation of cultural words in “Laskar Pelangi” into a Japanese novel, “Niji no Shoonentachi.” This research uses a descriptive approach with comparative models. Cultural words in this study are determined based on the classification proposed by Newmark’s models. In this research 186 data have been collected according to the two cultural categories, namely, material one and ecological one. The data collection was conducted by comparing Japanese: the target language, and Indonesian: the source language. This comparative analysis of the data uses work tools such as dictionaries, both printed and online. As a result, there are 161 equivalent and 25 not equivalent found out of the 186 data in the translation. The strategy used by the translator consists of literal translation, using general words, cultural substitution, couplet, naturalization from Indonesian, omission, descriptive, naturalization from English and calque. Meanwhile, the language style of the translator tends to follow the language style of the author, trying to bring out the aesthetic value of the source language. Following this tendency and this attitude, the translator of “Laskar Pelangi” has produced the good quality translation.